Penerapan Analisis Korelasi Kanonik pada Kajian Enso dalam Identifikasi Hubungan Fitur Iklim - Miftahuddin, Miftahuddin; Andriani, Ria; Setiawan, Ichsan; Mulsandi, Adi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2013)
There are several resulting arguments from the research done on climate variation in Indonesia stating that the observed affects are through various phenomena such as ENSO, monsoon, dipole mode event, and MJO. However, the magnitude of the effect varies for each region in Indonesia. This research aims to identify the relationship among the global climate features (GCFs) in the Nino3.4 (5°S–5°N, 120–170°W) with the local climate features (LCFs) in the Aceh regions which represented by: I(2–3°N, 95–98°E), II(3–4°N, 95–98°E), III(4–5°N, 95–98°E), and IV(5–6°N, 95–98°E) using canonical correlation analysis (CCA) in the ENSO phenomena. The analysis shows that global GCFs variations have strong correlation with LCFs variations with the correlation values, 0.893, 0.899, 0.900, and 0.901, respectively. The result show that when there is a global change in any feature of GCFs, the same change also appears in each feature of LCFs. The canonical loading shows that there are original variables which have strong correlation with the first canonical global variable (X1) with correlations 0.987, 0.969, 0.987, and 0.865,respectively, and the local wind (Y1) with correlations 0.974, 0.952, 0.979, and 0.845, respectively. All the other climate features have weak correlations with the first canonical variables. From the MANOVA, we can conclude that the climate features (wind, SST, SSTA, and SLP) affect climate changes in both study regions. Our results also reveal that LCFs are significantly affected in the Nino3.4 99.5% and in I, II, III, and IV for given correlations 99.8, 99.7, 99.6, and 99.5%, respectively.